Regulation of microvascular permeability by vascular endothelial growth factors* - Bates, DO (Blackwell Science Inc, 2002)
Generation of new blood vessels from pre-existing vasculature (angiogenesis) is accompanied in almost all states by increased vascular permeability. This is true in physiological as well as pathological angiogenesis, but is more marked during disease states. Physiological angiogenesis occurs during tissue growth and repair in adult tissues, as well as during development. Pathological angiogenesis is seen in a wide variety of diseases, which include all the major causes of mortality in the west: heart disease, cancer, stroke, vascular disease and diabetes. Angiogenesis is regulated by vascular growth factors, particularly the vascular endothelial growth factor family of proteins (VEGF). These act on two specific receptors in the vascular system (VEGF-R1 and 2) to stimulate new vessel growth. VEGFs also directly stimulate increased vascular permeability to water and large-molecular-weight proteins. We have shown that VEGFs increase vascular permeability in mesenteric microvessels by stimulation of tyrosine autophosphorylation of VEGF-R2 on endothelial cells, and subsequent activation of phospholipase C (PLC). This in turn causes increased production of diacylglycerol (DAG) that results in influx of calcium across the plasma membrane through store-independent cation channels. We have proposed that this influx is through DAG-mediated TRP channels. It is not known how this results in increased vascular permeability in endothelial cells in vivo. It has been shown, however, that VEGF can stimulate formation of a variety of pathways through the endothelial cell, including transcellular gaps, vesiculovacuolar organelle formation, and fenestrations. A hypothesis is outlined that suggests that these all may be part of the same process.